2013
DOI: 10.1002/wsbm.1216
|View full text |Cite
|
Sign up to set email alerts
|

Engineered genetic information processing circuits

Abstract: Cells implement functions through the computation of biological information that is often mediated by genetic regulatory networks. To reprogram cells with novel capabilities, a vast set of synthetic gene circuits has recently been created. These include simple modules, such as feedback circuits, feed-forward loops, ultrasensitive networks, band-pass filters, logic gate operators and others, with each carrying a specific information processing functionality. More advanced cellular computation can also be achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 135 publications
(72 reference statements)
0
21
0
Order By: Relevance
“…At a molecular level, information processing (Ausländer et al, 2012 ; Daniel et al, 2013 ) has been observed in numerous processes, such as the reversible phosphorylation of proteins (Thomson and Gunawardena, 2009 ); microtubule dynamics (Faber et al, 2006 ); enzymatic processes (Baron et al, 2006 ; Katz and Privman, 2010 ); redox regulation (Dwivedi and Kemp, 2012 ); transcription (Mooney et al, 1998 ); genetic regulatory networks (Qi et al, 2013 ); input signal transduction (Roper, 2007 ); biochemical networks (Bowsher, 2011 ); NF-kappaB dynamics (Tay et al, 2010 ); intracellular signaling reactions (Kamimura and Kobayashi, 2012 ; Purvis and Lahav, 2013 ); metabolic switches (Ramakrishnan and Bhalla, 2008 ); the chemotaxis pathway (Shimizu et al, 2010 ); network motifs (Alon, 2007 ), and other cellular processes (Ben-Jacob, 2009 ).…”
Section: Metabolic Network and Information Propertiesmentioning
confidence: 99%
“…At a molecular level, information processing (Ausländer et al, 2012 ; Daniel et al, 2013 ) has been observed in numerous processes, such as the reversible phosphorylation of proteins (Thomson and Gunawardena, 2009 ); microtubule dynamics (Faber et al, 2006 ); enzymatic processes (Baron et al, 2006 ; Katz and Privman, 2010 ); redox regulation (Dwivedi and Kemp, 2012 ); transcription (Mooney et al, 1998 ); genetic regulatory networks (Qi et al, 2013 ); input signal transduction (Roper, 2007 ); biochemical networks (Bowsher, 2011 ); NF-kappaB dynamics (Tay et al, 2010 ); intracellular signaling reactions (Kamimura and Kobayashi, 2012 ; Purvis and Lahav, 2013 ); metabolic switches (Ramakrishnan and Bhalla, 2008 ); the chemotaxis pathway (Shimizu et al, 2010 ); network motifs (Alon, 2007 ), and other cellular processes (Ben-Jacob, 2009 ).…”
Section: Metabolic Network and Information Propertiesmentioning
confidence: 99%
“…Activation of each phase is dependent on the proper progression and completion of the previous one, which can be monitored by cell cycle checkpoints. It is now believed that all proliferation, differentiation, and cell death processes are controlled by the underlying gene regulatory networks (5), which often involve many complex feedback loops (6). The complexity of the large regulatory networks for the cell cycle makes it difficult to understand the global natures and connections between the underlying network and the cell cycle process.…”
mentioning
confidence: 99%
“…For example, extended from the programming of cellular dynamics, synthetic bacterial systems have been applied to understand ecological and evolutionary questions that are difficult to address with natural communities [108]. Towards real-world applications, bacterial consortia synthesized with designer communication modules have been used for information processing [109,110], bio-computation [111], and therapeutics [112][113][114], as well as material and chemical productions [115][116][117]. There are a variety of research fields where synthetic bacterial consortia have started to play an important role: In metabolic engineering, cellular communication can be used to implement self-regulated control between cellular growth and product manufacturing in bioreactors for autonomous bioproduction.…”
Section: Discussionmentioning
confidence: 99%